Early Thirteenth-Century English Franciscan Thought - Schumacher, Lydia (Veröffentlichungen des Grabmann-Institutes zur Erforschung der mittelalterlichen Theologie und Philosophie, 2021)
During the 13th century, the Franciscan school became prominent among the first universities such as Oxford and Paris and other European centres of learning. This volume explores the contributions to scholarship of some of the major English Franciscans or Franciscan associates who worked primarily at Oxford, situating their contributions in relation to those of the other major Franciscan schools that existed at the same time, especially in Paris.